Present and future searches for leptoquarks - Eboli, OJP; Funchal, R. Z.; Lungov, T. L. (World Scientific Publ Co Pte Ltd, 1998)
We review the present searches for scalar leptoquarks and the potential of the CERN Large Hadron Collider (LHC) to unravel the existence of first generation leptoquarks.